The impact of forest degradation on carbon stocks of forests in the Matiwane area of the Transkei, South Africa - Mangwale, Kagiso (Rhodes University, Faculty of Science, Department of Environmental Science, 2011)
This study focused on assessing the condition and creating a carbon inventory of forests in the Matiwane area of the Transkei. This entailed the use of aerial photography in tracing forest cover change from 1942 to 2007 coupled with ground-truthing to assess whether the forests have in any way endured degradation over the years with a potential reduction in carbon stocks as a result. This study revealed both the loss and gain of biomass in the area with a general trend of forests being continuously converted to agricultural fields resulting in reduced forest area, stem density, tree density and carbon loss in different pools of the forests, reflecting that these forests are degraded. The conversion has resulted in the reduction in the number of species from a mean of 11Â±0.57 species/200mÂ² in intact forests to 1Â±0.23species/200mÂ² plot in degraded forests. It was also revealed that approximately 5.2 % (791 hectares) of 15 352 hectares of forest area was lost as a result of the conversion of forest land to agricultural fields from 1942 to 2007 with 99 % of the clearing occurring in the last 33 years (1974-2007) and of which 60 % ( 4 77 hectares) occurred from 1995 to 2007, indicating that forest degradation in these forests is on the increase. The assessment also revealed some areas that were nonforest in 1942 that have accumulated woody biomass (BAA), composed mainly of Acacia sp accounting for 51.18 MgC.haâ »Â¹ (Megagrams of carbon per hectare) and total carbon stocks of 0.02 TgC (Teragrams of carbon). The degradation of these forests induced a reduction in carbon stocks from 311.68Â±23.69 MgC.haâ »Â¹ (to a soil depth 0-50 cm) in intact forest to 73.46Â±12.34 MgC.haâ »Â¹ in degraded forests. The total carbon stocks in the degraded forests were approximated at 0.06 TgC and the BAA areas 0.02 TgC with 4.7 TgC in intact forests. The degradation of these forests has resulted in the net carbon loss of 0.19 TgC between 1942 and 2007 but 4.76 TgC is still locked in these forests. The large difference in carbon stocks between intact and degraded forests indicated the need to reduce the degradation of these forests to prevent further carbon loss and reduction of the carbon sequestration potential of these forests.
Keywords: Forest degradation -- Control -- South Africa -- Transkei; Forest ecology -- South Africa -- Transkei; Carbon sequestration -- South Africa -- Transkei; Forest conservation -- South Africa -- Transkei